Modeling of 1D confinement in FD-SOI trigate nanowires at deep cryogenic temperatures. (December 2022) - Catapano, E.; Cassé, M.; Gaillard, F.; Meunier, T.; Vinet, M.; Ghibaudo, G.
Highlights: Multi-gate FD-SOI qubit MOS devices were electrically characterized. At deep cryogenic temperatures and in linear regime, oscillations in both the current and the transconductance were observed above threshold. These are likely related to the formation of one-dimensional sub-bands in the silicon active region. A compact model taking into account a 1D density of states (DOS) has been developed in order to fathom how the 1D confinement influences both the inversion charge and the transconductance. Furthermore, the impact of drain voltage was also investigated, showing that the oscillations were smoothed out at high drain biases. Abstract: Multi-gate FD-SOI qubit MOS devices were electrically characterized. At deep cryogenic temperatures and in linear regime, oscillations in both the current and the transconductance were observed above threshold. These are likely related to the formation of one-dimensional sub-bands in the silicon active region. A compact model taking into account a 1D density of states (DOS) has been developed in order to fathom how the 1D confinement influences both the inversion charge and the transconductance. The impact of temperature was shown to be crucial in order to distinguish the sub-bands contribution to the transconductance oscillations. Furthermore, the impact of drain voltage was also investigated, showing that the oscillations were smoothed out at high drain biases.